The influence of the type of birth and the mother´s diet on the breastfeeding period. - Daniela Benites; Erissandra Gomes; Márcia Cançado; Ingrid de Lima; Fernanda Wisniewski; Fabiana Carletto-Körber (Universidad de Concepción., 2014)
The prenatal aspects may influence the duration of breastfeeding of newborns, which when reduced harm to their development brings cranio-orofacial. Correlate the type of delivery and maternal diet with breastfeeding period. This was a descriptive study based on the records of the medical records of 820 dyads of mothers and newborns participating in the University Extension Baby Clinic. The results were analyzed, considering a significance level of 5%. The absence of complications during pregnancy was a positive factor for the occurrence of vaginal delivery in 94% of the sample (p<0.001). It was found a high percentage of cesarean delivery (43%). The number of caesarean sections in women with cariogenic diet was higher than in women with non-cariogenic diet. The women who have a cariogenic diet does not have a tendency to breastfeed their children for more than 6 months (p<0.01). Also there was an association between vaginal delivery and longer period of 6 months of breastfeeding (p<0.001). The collected sample mode of delivery and maternal diet influence the duration of breastfeeding.